ANALISIS LIKUIFAKSI AKIBAT GEMPA PADA PEMBANGUNAN TOWER TRANSMISI 150 kV PLTU. LABUHAN ANGIN SIBOLGA - Masriani Endayanti; Junihar Bintang (JURNAL ILMIAH TEKNIK SIPIL, 2021)
One of the impacts of earthquakes is the loss of strength of the soil layer due to vibrations called liquefaction. Liquefaction generally occurs in poorly graded sandy soils. This kind of soil is found in the construction of the 150 kV Transmission Tower of the Labuhan Angin Sibolga PLTU. Therefore, the analysis of the potential for liquefaction is an important thing to do in the design of the transmission tower foundation. Geological threats, especially liquefaction events during large earthquakes on earthquake-prone routes, are something that can occur, and can cause extensive damage to buildings and infrastructure. Labuhan Angin Sibolga is an earthquake-prone area, where a 150 kV Transmission Tower was built with a loose sand-graded soil texture. To withstand the weight of a heavy building on the ground, a solid foundation is needed. If the soil conditions on the surface are not able to withstand the building, then the building load must be transferred to the hard soil layer below it. For this reason, deep foundation construction is used for the construction of the 150 kV Transmission Tower at PLTU Labuhan Angin Sibolga. The bore pile foundation planner must be able to bear vertical forces, horizontal forces and moments that occur due to lateral deformation caused by liquefaction. Sufficient resistance to carry this load can be obtained from the larger and stiffer pile dimensions, so the pile diameter is 60 cm. Based on the results of soil inspection (sondir test), for this transmission tower, bore pile foundation type (4 pile configuration) is obtained at a depth of 10 m with total skin friction Tf = 721.80 kg/cm (sondir data), diameter 60 cm.